2014
DOI: 10.12944/cwe.9.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Do Extensive Rubber Plantation Influences Local Environment ? A Case Study from Tripura, Northeast India

Abstract: Tripura is the second largest Natural Rubber (NR) producing state of India. As most of the NR plantation in the state is rain dependent, it is observed that fluctuation in monsoon poses a serious threat to plantation growth. The effect of such shift and fluctuation in climate ranges from surface and ground water level variation, air quality and soil preservation. At present no assessment is available to critically review the impact of large scale NR plantation on environment. In the present paper the effect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Rubber plantation which contributes less in the morning contributes more to high more than public facilities and classroom building. It means -unlike the other vegetation vegetation in rubber plantation give bad the local environment (Majumder et al, 2014 road network in the noon contributes more than itself in the morning. It is suggested that the traffic at the noon is more than the traffic in the morning including road network inside campus road close to the southwest water body body contributes more than classroom building since it reflects solar energy into the surroundings.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Rubber plantation which contributes less in the morning contributes more to high more than public facilities and classroom building. It means -unlike the other vegetation vegetation in rubber plantation give bad the local environment (Majumder et al, 2014 road network in the noon contributes more than itself in the morning. It is suggested that the traffic at the noon is more than the traffic in the morning including road network inside campus road close to the southwest water body body contributes more than classroom building since it reflects solar energy into the surroundings.…”
Section: Resultsmentioning
confidence: 98%
“…unlike the other vegetation -the vegetation in rubber plantation give bad impact on Majumder et al, 2014). The road network in the noon contributes more than itself in the morning.…”
Section: Resultsmentioning
confidence: 99%
“…Environmentalists tend to believe that planting rubber will induce more carbon release, lead to severe drought, and harm the environment, whereas the government states that rubber plantations are forests just like any other natural forest and will not cause any threat to the environment. The details of rubber plantation on microenvironment have been recently assessed 2 . Rubber plantation will provides an effective tool for enhancing the economic, social and environmental values but, further investigation on the of socioeconomic and environmental sustainability of rubber plant should further be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades , global demand for tree cash crop products has increased dramatically, for example a production area for rubber has increased by 143% (9.4 Million hectare) 1 . Despite the large extension of land covered by rubber, the environmental and socioeconomics impacts of rubber expansion have recently been explored at various scales 2,3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the problems already faced by smallholders, rubber plantations are also exposed to other production challenges. These include pests and diseases [13][14][15][16][17]; poor agricultural management practices [18]; competition for land [16,19] and more recently, worldwide rapid expansion into unsuitable agricultural sites [20][21][22][23][24]. Effective plantation management and monitoring is therefore vital to ensure sustainable rubber production.…”
Section: Introductionmentioning
confidence: 99%